US publishing as a cultural phenomenon: history, current realities and prospects - Zhyvohliadova, Iryna; Пузирко, (Ukrainian Cultural Studies, 2022)
The article analyses the specifics of the formation of the American publishing system in the context of the incipience of national culture and statehood. It highlights the importance of print production as an important component of the overall system for the formation and maintenance of the original face of the United States – both in the early stages of the formation of the state and culture, as well as in modern realities, complicated by the Covid pandemic situation. The US publishing system is at the forefront of technological changes that affect both American and world reading and book culture: not only the diversity and democratisation of the form of consumer culture, but also the quality of the media sphere as a special space for the life of a modern person. The experience of the American book market, the US publishing industry is considered, demonstrating the importance of publishing as a meaningful tool for socialisation and inculturation, its significant influence on the formation of national traditions of  "bookishness", reading culture, and on the level of the general cultural education of the nation.
Keywords: national culture; American book market; US publishing production; book culture; printed book; cultural practice; mediasphere